2007
DOI: 10.1186/1475-2867-7-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of stem cells in cancer therapy and cancer stem cells: a review

Abstract: For over 30 years, stem cells have been used in the replenishment of blood and immune systems damaged by the cancer cells or during treatment of cancer by chemotherapy or radiotherapy. Apart from their use in the immuno-reconstitution, the stem cells have been reported to contribute in the tissue regeneration and as delivery vehicles in the cancer treatments. The recent concept of 'cancer stem cells' has directed scientific communities towards a different wide new area of research field and possible potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(88 citation statements)
references
References 113 publications
0
82
0
3
Order By: Relevance
“…It has been shown that chemotherapy can induce inhibitory factors such as Tumor Growth Factor(TNF)-α and Interleukin(IL)-4 with cytokines that causes myelosupression. The adequate number of the stem cells therapy is also reported crucial factors for speedy recovery [49]. Therefore, based on above conclusion the following recommendations are forwarded:…”
Section: Stem Cells In Immuno-reconstitutionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that chemotherapy can induce inhibitory factors such as Tumor Growth Factor(TNF)-α and Interleukin(IL)-4 with cytokines that causes myelosupression. The adequate number of the stem cells therapy is also reported crucial factors for speedy recovery [49]. Therefore, based on above conclusion the following recommendations are forwarded:…”
Section: Stem Cells In Immuno-reconstitutionmentioning
confidence: 99%
“…The potential of stem cell therapies has long been recognized and the creation of iPSC has boosted the stem cell field leading to increasing development and scientific knowledge [39]. For over 30 years, stem cells have been used in the replenishment of blood and immune systems damaged by the cancer cells [49].…”
Section: Role Of Stem Cell Therapy In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…CSCs are a small population present in cancer cells with unique properties: i) self-renewal capability, ii) cell differentiation ability and iii) cancer initiation potential (33,34). These properties of CSCs contribute to chemoradiotherapy resistance and cause tumor recurrence.…”
Section: The Resistance Mechanisms Of Cscsmentioning
confidence: 99%
“…Trials are on the way to treat various diseases. Stem cell transplant is considered as an option for the treatment of certain type of cancers [19]. This medical procedure can also be used to treat neurological diseases [20], autoimmune diseases [21], restoration of sight [22], wound healing [23], heart diseases [24], liver diseases [25], metabolic disorders [26], spinal cord injury [27] etc.…”
Section: Stem Cell Transplantmentioning
confidence: 99%